TECHNOLOGY OF USING ELEMENTS OF SPORTS GAMES IN IMPROVING THE PHYSICAL FITNESS OF 7-8-YEAR-OLD STUDENTS - Ernazar Jurayevich Kholmirzayev (Web of Journals Publishing, 2023)
This article is dedicated to the use of effective methods of movement games in the process of physical fitness activities on the educational agenda to increase the physical fitness of 7–8-year-old students in physical education classes and to plan movement games in fitness activities.
Keywords: movement games, physical culture, physical education, basketball, volleyball, handball, football, organism, physical training.